Climate Change Frame Production: Perspectives from Government Ministers and Senior Media Strategists in Ireland. Issue 4 (18th May 2020) - Robbins, David
ABSTRACT: Research into media frames has focused extensively on the frames found in media texts, while the frame production processes which occur prior to publication have been relatively neglected. Little is known, for instance, about the framing strategies deployed by elite actors in order to influence media coverage of their chosen issue. Taking the case of elite, government-level communication concerning climate change in Ireland, this research presents data from a series of in-depth interviews with two Green Party government ministers, and their senior media advisors, concerning their approach to communicating with journalists about climate change. The interview subjects framed their communications intuitively rather than strategically, but the ways in which they discussed the presentation of their policies maps onto existing frame typologies. The ministers and their advisors employed disparate approaches to communicating about climate change, and they lacked a coherent and disciplined framing strategy. This paper concludes that ministers' efforts to persuade the media to adopt their preferred framing of climate change was negatively affected by the internal conflict over how best to frame the issue, and argues that the failure to resolve the internal frame competition may be just as important as the external competition to influence journalistic framings.